Fracture healing in the elderly: A review. - Foulke, B; Kendal, A; Murray, D; Pandit, H (Elsevier, 2016)
Older patients are commonly at a higher risk of experiencing a bone fracture. Complications during fracture healing, including delayed union and non-union, can arise as a result of a multitude of patient and treatment factors. This review describes those factors which contribute to a greater risk of delayed union and non-union with particular reference to the elderly population and discusses therapies that may enhance the fracture healing process in the hope of reducing the incidence of delayed union and non-union. Increasing age does seem to increase the risk of delayed union or non-union. In addition, smoking and the treatment of post-fracture pain with non-steroidal anti-inflammatory drugs (NSAIDs) put the patient at the greatest risk, while ultrasound therapy appears to be a non-invasive, effective treatment option to reduce the risk of delayed union or non-union. The use of growth factors and of stem cells and the role of surgery are also discussed.